Characterization of a Hyaluronic Acid Utilization Locus and Identification of Two Hyaluronate Lyases in a Marine Bacterium Vibrio alginolyticus LWW-9 - Wang, Xiaoyi; Wei, Ziwei; Wu, Hao; Li, Yujiao; Han, Feng; Yu, Wengong (Frontiers in Microbiology, 2021)
Hyaluronic acid (HA) is a negatively charged and linear polysaccharide existing in the tissues and body fluids of all vertebrates. Some pathogenic bacteria target hyaluronic acid for adhesion and/or infection to host cells. Vibrio alginolyticus is an opportunistic pathogen related to infections of humans and marine animals, and the hyaluronic acid-degrading potential of Vibrio spp. has been well demonstrated. However, little is known about how Vibrio spp. utilize hyaluronic acid. In this study, a marine bacterium Vibrio alginolyticus LWW-9 capable of degrading hyaluronic acid has been isolated. Genetic and bioinformatic analysis showed that V. alginolyticus LWW-9 harbors a gene cluster involved in the degradation, transport and metabolism of hyaluronic acid. Two novel PL8 family hyaluronate lyases, VaHly8A and VaHly8B, are the key enzymes for the degradation of hyaluronic acid. VaHly8A and VaHly8B have distinct biochemical properties, reflecting the adaptation of the strain to the changing parameters of the aquatic habitats and hosts. Based on genomic and functional analysis, we propose a model for the complete degradation of hyaluronic acid by V. alginolyticus LWW-9. Overall, our study expands our knowledge of the HA utilization paradigm within the Proteobacteria, and the two novel hyaluronate lyasesare excellent candidates for industrial applications.